Correlation between polymorphism in the inosine triphosphatase and the reductions in hemoglobin concentration and ribavirin dose during sofosbuvir and ribavirin therapy. Issue 8 (August 2017) - Kozuka, Ritsuzo; Hai, Hoang; Teranishi, Yuga; Motoyama, Hiroyuki; Kawamura, Etsushi; Hagihara, Atsushi; Uchida‐Kobayashi, Sawako; Morikawa, Hiroyasu; Enomoto, Masaru; Murakami, Yoshiki; Kawada, Norifumi; Tamori, Akihiro
Abstract: Background and Aim: It is unclear whether polymorphism in the inosine triphosphatase ( ITPA ) gene correlates to the reduction in hemoglobin (Hb) concentrations during sofosbuvir (SOF) and ribavirin (RBV) therapy. This study investigated the effects of the ITPA polymorphism on Japanese patients with chronic hepatitis C virus genotype 2 infection treated with SOF/RBV therapy. Methods: In 106 patients treated with SOF/RBV therapy, this study assessed the effects of the ITPA polymorphism (rs1127354) on anemia, RBV dose reduction, and sustained virological response. Results: Of the 106 patients, 80 had the CC genotype, whereas 26 had a non‐CC genotype in ITPA . Patients with the CC genotype had significantly larger reductions in Hb concentrations than those with a non‐CC genotype throughout the treatment course. RBV dose reduction was required in 18/106 (17.0%) patients, with a significantly higher frequency in patients with the CC genotype than in those with a non‐CC genotype ( P  = 0.010). In multivariate analysis, age ≥ 65 years ( P  = 0.011) and the ITPA CC genotype ( P  < 0.0001) were factors significantly associated with anemia throughout the treatment course. Sustained virological response was achieved in 99.0% of all patients: 98.7% of patients with the CC genotype and 100% of patients with a non‐CC genotype. Conclusions: Inosine triphosphatase polymorphism appeared to correlate with anemia incidence and RBV dose reduction during SOF/RBV therapy, but not the clinical outcome. Careful monitoring of Hb concentrations and prompt adjustment of RBV doses are required for successful treatment, particularly in patients harboring the ITPA CC genotype or age ≥ 65 years.